Life cycle assessment of biofuel production from microalgae cultivated in anaerobic digested wastewater - Li, Gang; Lu, Zhitao; Zhang, Jiang; Li, Huan; Zhou, Yuguang; Zayan, Ali Mohammed Ibrahim; Huang, Zhigang (International Journal of Agricultural and Biological Engineering, 2020)
The whole process of biofuel production from Desmodesmus sp. EJ 8-10 cultivated in anaerobic digested wastewater (ADW) under the optimal temperature was evaluated by using the method of Life Cycle Assessment (LCA). The energy efficiency and environment emissions were under considerable for the corresponding parametric study. The functional unit was 1 kg microalgae. It was concluded that the harvest stage was responsible for the main energy consumption during the microalgal whole pyrolysis process. The energy conversion efficiency of the whole process was larger than 1, which indicated that the process was profitable. The environmental impact of the whole process was 1165.67 mPET2000, among which the primary impact on the environment was eutrophication that accounts for 57.36%, followed by photochemical ozone synthesis (22.56%), acidification (17.36%); and global warming (2.73%), respectively. Keywords: microalgae, fast pyrolysis, life cycle assessment (LCA), anaerobic digested wastewater (ADW), biofuel production DOI: 10.25165/j.ijabe.20201301.4178 Citation: Li G, Lu Z T, Zhang J, Li H, Zhou Y G, Zayan A M I, et al. Life cycle assessment of biofuel production from microalgae cultivated in anaerobic digested wastewater. Int J Agric & Biol Eng, 2020; 13(1): 241–246.